A sintering and carbon-resistant Ni-SBA-15 catalyst prepared by solid-state grinding method for dry reforming of methane. (January 2017) - Zhang, Qiulin; Zhang, Tengfei; Shi, Yuzhen; Zhao, Bin; Wang, Mingzhi; Liu, Qixian; Wang, Jing; Long, Kaixian; Duan, Yankang; Ning, Ping
Graphical abstract: Ni-SBA-15 was prepared by solid-state grinding method and applied to the dry reforming of methane. Coking and sintering were inhibited simultaneously by the strong interaction between the well-dispersed Ni species and SBA-15. The conversions of CO2 and CH4 over Ni-SBA-15 showed remarkably stable even reacted at 700 °C for 100 h. Highlights: The DRM catalytic performance over Ni-SBA-15 showed remarkably stability. No obvious carbon deposition was detected over the Ni-SBA-15. The Ni sintering was greatly suppressed by strong metal-support interaction. The average crystalline size of the Ni particles size was ∼3.2 nm on Ni-SBA-15. Abstract: Nickel-containing ordered mesoporous silica materials (Ni-SBA-15, Ni-KIT-6 and Ni-MCM-41) were prepared by solid-state grinding method and applied to the dry reforming of methane (DRM). After reacting at 700 °C for 100 h, the catalytic activity and stability declined in the following sequence: Ni-SBA-15 > Ni-KIT-6 > Ni-MCM-41. The characterization results indicated that the average size of the Ni particles on Ni-SBA-15 was ∼3.2 nm, and no visible NiO diffraction peak observed on Ni-SBA-15, implying that the nickel species were highly dispersed on the SBA-15. Moreover, the reduction temperature of Ni species on Ni-SBA-15 obviously shifted to higher temperature compared with the Ni/SBA-15 prepared by impregnation method, indicating that the interaction between the Ni species and mesoporous support was enhanced. The Ni-SBA-15 also presented excellent resistance to the carbon deposition, and the carbon deposition decreased in the order of Ni-MCM-41 (38.8%) > Ni-KIT-6 (8.1%) > Ni-SBA-15 (6.3%) after reacting at 700 °C for 100 h.